2014
DOI: 10.3390/su6074077
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Corporate Social Responsibility and Financial Performance in the Mineral Industry: Evidence from Chinese Mineral Firms

Abstract: This paper examines the relationship between Corporate Social Responsibility (CSR) and Corporate Financial Performance (CFP) using panel data for 228 Chinese mineral listed firms from 2010 to 2013 with Pooled Least Squares regression analysis. Our study considers five different sublevel CSR issues-shareholder responsibility, employee responsibility, environmental responsibility, public responsibility, and supplier, customer and consumer responsibility-in capturing the effects of CSR elements on CFP. The estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
3
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 45 publications
(45 reference statements)
8
72
3
10
Order By: Relevance
“…The positive effect of CSR on financial performance is consistent with many studies conducted in Western, Asian, and other countries (e.g., [4,[16][17][18]43]). Additionally, in the context of Zambia, Choongo et al [20] established that SMEs are motivated to engage in CSR for financial benefits.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The positive effect of CSR on financial performance is consistent with many studies conducted in Western, Asian, and other countries (e.g., [4,[16][17][18]43]). Additionally, in the context of Zambia, Choongo et al [20] established that SMEs are motivated to engage in CSR for financial benefits.…”
Section: Discussionsupporting
confidence: 75%
“…While some studies also show negative or neutral effects, overall, extant literature postulates that CSR impacts firm performance positively. Pan, Sha, Zhang, and Ke [18] observed that employee responsibility and environmental responsibility have significant positive relationships with corporate financial performance. Lee, Herold, and Yu [55] suggested that SMEs are motivated to pursue CSR activities when they perceive a business benefit and value for the company.…”
Section: Financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that there is a positive correlation between CSR and CFP. Pan et al (2014) assessed the relationship between CSR and Corporate Financial Performance (CFP) of 288 Chinese mineral listed firms from 2010-2013 by using Pooled Least Square Regression analysis. They have considered CSR issues in five different sub issues and out of them shareholder responsibility, employee responsibility, supplier, customer responsibility have significant relationship with CFP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In turn, China is rapidly becoming a key player in the global market, and what China does in the realm of CSR reporting will affect many companies around the world through the global supply chain. There have been many studies that try to identify the drivers of CSR reporting and practice, including those focused on corporate reputation, brand value, and financial performance [1][2]. Reputation is a very important signal to the public about a company's products, jobs, and strategies in a competitive market.…”
Section: Introductionmentioning
confidence: 99%